On a New Stability Problem of Radical nth-Degree Functional Equation by Brzdęk's Fixed-Point Method. (25th June 2019) - Kang, Dongseung; Kim, Hoewoon B.
Abstract : In this paper, we introduce the radicaln th-degree functional equation of the formf ( x n + y n n ) = f ( x ) + f ( y ) with a positive integern, discuss its general solutions, and prove new Hyers-Ulam-type stability results for the equation by using Brzdęk's fixed-point method.